Novel Applications of Intelligent Systems - Hadjiski, Mincho; Kasabov, Nikola; Filev, Dimitar; Jotsov, Vladimir; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
In this carefully edited book some selected results of theoretical and applied research in the field of broadly perceived intelligent systems are presented. The problems vary from industrial to web and problem independent applications. All this is united under the slogan: "Intelligent systems conquer the world". The book brings together innovation projects with analytical research, invention, retrieval and processing of knowledge and logical applications in technology. This book is aiming to a wide circle of readers and particularly to the young generation of IT/ICT experts who will build the next generations of intelligent systems.
Modern Approaches for Grain Quality Analysis and Assessment -- Intelligent Technical Fault Condition Diagnostics of Mill Fan -- Abstraction of State-Action Space Utilizing Properties of the Body and Environment -- Trajectory Control of Manipulators Using an Adaptive Parametric Type-2 Fuzzy CMAC Friction and Disturbance Compensator -- An Evaluation of OWL-based Semantic Applications -- On Heading Change Measurement: Improvements for Any Angle Path-Planning -- CxK-Nearest Neighbor Classification with Ordered Weighted Averaging Distance -- ARTOD: Autonomous Real Time Objects Detection by a Moving Camera using Recursive Density Estimation -- Improved Genetic Algorithm for Downlink Carrier Allocation in an OFDMA System -- Structure-oriented Techniques for XML Document Partitioning -- Security Applications Using Puzzle and Other Intelligent Methods -- Semiautomatic Telecontrol by Multi-link Manipulators Using Mobile Telecameras -- Vision-Based Hybrid Map-Building and Robot Localization in Unstructured and Moderately Dynamic Environments --  Innovative Fuzzy-Neural Model Predictive Control Synthesis for Pusher Reheating Furnace -- Exactus Expert-Search and Analytical Engine for Research and Development Support.-Acoustic and Device Feature Fusion for Load Recognition.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence